The application of the soft modeling method to evaluate changes in customer behavior towards e-commerce in the time of the global COVID-19 pandemic - Anna Dewalska-Opitek; Katarzyna Bilińska; Marek Cierpiał-Wolan (Risks, 2022)
As a result of the COVID-19 pandemic, business and consumer behavior towards online consumption and digital payments has changed. This trend, although significant, may be observed, to a varying extent, among customers across the European Union. This study aims to investigate if, and to what extent, the COVID-19 pandemic has had a powerful impact on online consumer behavior in EU (European Union) countries. The empirical research using a soft modeling method supplements theoretical deliberations based on critical literature review. A conceptual model was adopted. Three first-order latent variables were selected for the analysis: "online customer behavior", "online activity" and "willingness to spend online", to which all analyzed indicators (14) were classified. The analysis of the loadings of latent variables for 2019 and 2020 allowed the impact of the pandemic on customer behavior to be observed, although this was not the same across all EU countries. Clustering performed with the hit map enabled the identification of four groups of countries. Significant changes in behavior were observed in countries such as Poland, Ireland, Romania, Hungary, Slovenia, Spain, and Finland. The results of the classification based on the values of three latent variables indicate that only the composition of one group (Bulgaria and Romania) remained unchanged during the study period. Research discussion was presented, and further fields of study were identified.
Keywords: 330; current trends during COVID-19 pandemics; online customer behavior; soft modeling method